İNFORMACIYALARDÍ SISTEMALASTÍRÍW USÍLLARÍ - Abdullaev, A.; Juginisova, J. (SCIENCE and SOCIETY, 2016)
The article deals with the issues of scientific-methodical supply of the information systematization. The author describes the algorithm of preservation of the information in the form of an electronic table on the basis of MS Excel. The received results are used in the 8-th form, they correspond to themes of sorting and information filtration. There have been worked out innovative technologies of systematization of the information.